Pengaruh edukasi tentang teledentistry terhadap peningkatan pengetahuan mahasiswa fakultas kedokteran gigi (Laporan Penelitian) - Kiara Maulika Azuri; Lia Hapsari Andayani (Jurnal Kedokteran Gigi Terpadu, 2022)
The use of e-health keeps growing during the Coronavirus Disease 2019 (COVID-19) pandemic. To reduce the risk of on-site transmission in dental clinic, health care providers can minimize face to face meetings by implementing teledentistry using video conferencing technology from distant. The use of teledentistry is a technological development that is needed in dental and oral health services. Therefore, it is important for dental students as future dentists to have proper knowledge about the application of teledentistry in dental practice. The research method used in this study is a quasi-experimental design using the one-group pretest-posttest design which was conducted online on 75 dental students of Universitas Trisakti Class 2017. Respondents were given 10 minutes to fill out the pretest, before getting an explanation of the material about teledentistry using power point text media. The materials provided are definitions, methods, types and benefits of teledentistry. After that, respondents were given 6 minutes to fill out the posttest. The results showed that the mean (± standard deviation) of pretest scores of 75 students was 7,85 (±1,658), which increased to 9,88 (±1,823) on the posttest (p=0,000). It can be concluded that the educational intervention proved to be effective at improving respondents’ knowledge of teledentistry.